THE PRINCIPLE OF LEGALITY AND THE REQUIREMENTS OF LAWFULNESS AND PROCEDURAL RATIONALITY Law Society of South Africa v President of the RSA (2019 (3) SA 30 (CC)) - Warren Freedman; Nkosinathi Mzolo (Obiter, 2021)
Apart from conferring a wide range of powers on the President, the Constitution also regulates the manner in which the President may exercise these powers. One of the ways in which the Constitution does this is by imposing an obligation on the President to exercise his or her powers in accordance with the principle of legality, which is an incident of the rule of law. A necessary consequence of this requirement is that a decision of the President may be reviewed and set aside on the grounds that it infringes the principle of legality.From its relatively modest beginnings in Fedsure Life Insurance v Greater Johannesburg Transitional Metropolitan Council (1999 (1) SA 374 (CC)) – where the Constitutional Court held that the exercise of public power is only legitimate when it is lawful – the principle of legality has expanded in leaps and bounds over the past 21 years; today, it encompasses several other grounds of review, including lawfulness, rationality, undue delay and vagueness.Of all of these broad grounds of review, substantive rationality has received the most attention from the courts and today encompasses several other grounds of review itself, such as procedural fairness, procedural rationality, relevant and irrelevant considerations (Democratic Alliance), non-jurisdictional mistake of fact, and, on occasion, the giving of reasons.Unfortunately, the development of the principle of legality has not been all plain sailing, and the rationality jurisprudence of the Constitutional Court has given rise to complex and difficult questions. This is particularly the case when it comes to procedural fairness and procedural rationality. It is not entirely clear what the difference between these two requirements is and in what circumstances the one should be applied rather than the other. The court attempted to address some of these questions in Law Society of South Africa v President of the Republic of South Africa (2019 (3) SA 30 (CC)) (Law Society). The purpose of this note is to discuss this case critically.